Assessing drug and metabolite detection in liver tissue by UV-MALDI and IR-MALDESI mass spectrometry imaging coupled to FT-ICR MS - Barry, Jeremy A. (Int J Mass Spectrom, 2014)
Determining the distribution of a drug and its metabolites within tissue is a key facet of evaluating drug candidates. Drug distribution can have a significant implication in appraising drug efficacy and potential toxicity. The specificity and sensitivity of mass spectrometry imaging (MSI) make it a perfect complement to the analysis of drug distributions in tissue. The detection of lapatinib as well as several of its metabolites in liver tissue was determined by MSI using infrared matrix-assisted laser desorption electrospray ionization (IR-MALDESI) coupled to high resolving power Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometers. IR-MALDESI required minimal sample preparation while maintaining high sensitivity. The effect of the electrospray solvent composition on IR-MALDESI MSI signal from tissue analysis was investigated and an empirical comparison of IR-MALDESI and UV-MALDI for MSI analysis is also presented.